From loop-holes to labour: Aboriginal connections to Calperum and Chowilla pastoral stations, South Australia. Issue 2 (3rd July 2021) - Roberts, Amy; Burke, Heather; Tutty, Megan; Westell, Craig; Aboriginal Corporation (RMMAC), the River Murray and Mallee
ABSTRACT: This paper examines Aboriginal connections to pastoral properties on the western central Murray River, with a focus on Calperum and Chowilla Stations. Station histories are presented, oral histories are explored and archaeological sites and material culture from the period are considered. The range of histories, interactions and "zones of encounter" are then compared to relevant interpretive models in order to highlight some of the myriad complexities relating to invasion, colonisation and pastoralism. In particular, we explore a range of themes, including conflict/violence, place names, traditional activities, rations, labour and more to demonstrate Aboriginal engagements and connection to Country throughout the pastoral era, even during times of significant duress – bringing to the fore otherwise "anonymised", "hidden" and "contested" narratives. This research was undertaken in collaboration with the River Murray and Mallee Aboriginal Corporation (RMMAC).